PENGARUH GOOD CORPORATE GOVERNANCE DAN FINANCIAL DISTRESS TERHADAP TAX AVOIDANCE DENGAN STRATEGI BISNIS SEBAGAI PEMODERASI (Studi Empiris pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Wahyu Ade Setianingrum; Herry Laksito (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of Good Corporate Governance (GCG) and financial distress on tax avoidance, with business strategy considered as a moderating variable. The independent variables in this study consist of institutional ownership and audit quality as indicators of GCG, as well as financial distress. The dependent variable is tax avoidance, while business strategy (Loan to Deposit Ratio) is used as the moderating variable.A quantitative method with a multiple linear regression approach was employed. The data used were obtained from the financial statements of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period.The results show that audit quality has a negative and significant effect on tax avoidance, while financial distress has a positive and significant effect on tax avoidance. Meanwhile, institutional ownership does not have a significant effect on tax avoidance. Furthermore, business strategy does not moderate the relationship between institutional ownership, audit quality, and financial distress with tax avoidance.